Molecular Bases of Diabetes Mellitus and its Relationship with non-enzymatic Glycosylation and Oxidative Stress - Dayamí García Torres; María de Jesús Sánchez Bouza; Pedro Javier Sánchez Sánchez; Pedro Sánchez Frenes; Laura Naranjo Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
The term diabetes mellitus defines metabolic alterations of multiple etiologies characterized by chronic hyperglycemia and disorders in the metabolism of carbohydrates, fats, and proteins, resulting from defects in insulin secretion, insulin action, or both. When insulin binds to its receptor, it triggers multiple molecular signaling pathways, which mediate its biological actions. Alterations in the receptor or downstream effect or molecules cause increased levels of glucose in the blood. Non-enzymatic glycosylation phenomena occur spontaneously in the human body, favoring the formation of free radicals. This review presents an update on the relationship between the molecular bases of insulin actions and the mechanisms involved in regulating its effects with non-enzymatic glycosylation processes and concomitant oxidative stress. The study of these interrelationships and their metabolic links will allow a better understanding of the causes associated with the complications of this entity.